ISU GLOBAL KONTEMPORER DALAM BISNIS DAN ORGANISASI - Irsan, Nuri Ahli Taqwa; Isrososiawan, Safroni (Jurnal Manajemen Dayasaing, 2025)
Abstract This study aims to determine global and contemporary issues in business and organizations. This study uses a qualitative method with a Library Research approach. The results show that global and contemporary issues in business and organizations are part of the impact of globalization. Several countries across continents can conduct international trade according to their respective motives, thus creating different business strategies and climates in each country. Countries in the Americas and Europe tend to create a disciplined business climate. Some contemporary issues in business are brand issues, integration of technological developments, consumer behavior, environmental change issues, and business tactics issues. The implications of this study as a reference for future related research.